Distribusi Pencabutan Gigi Akibat Karies Berdasarkan Karakteristik Sosiodemografi pada Pasien Poli Gigi Puskesmas Tanah Grogot Tahun 2017-2019: Distribution of Tooth Extraction Due to Caries Based on Sociodemographic Characteristics in Dental Polyclinic Patients at Tanah Grogot Public Health Center 2017-2019 - Aulya Rahma Fadilah; Portuna Putra Kambaya; Nydia Hanan (Jurnal Sains dan Kesehatan, 2022)
Dental caries is the most common condition in the oral cavity, especially in poor oral hygiene. In Riskesdas data, it is stated that caries become the largest proportion of dental problems in Indonesia, around 45.3%. In East Kalimantan, especially in Paser Regency, 53.02% of the population has complaints of cavities. People often consider tooth extraction an option in case of tooth decay, especially caries. This is due to the influence of culture and people's belief that tooth extraction will solve the problem. Various studies state that tooth loss due to extraction is caused by caries and is associated with influences on a person's characteristics such as age, gender, and occupation. The study aims to determine the distribution of tooth extraction due to caries based on sociodemographic characteristics in poly dental patients of Tanah Grogot health center in 2017-2019. This research is a descriptive method using medical record data subjects based on predetermined inclusion criteria. The data are grouped based on sociodemographic characteristics (age, gender, occupation) and tooth regio removed. The data are grouped based on sociodemographic characteristics and tooth regio removed. The results are presented in the form of tables and narrations. Age 35-44 years as many as 44 patients (26.38%) and female gender of 97 patients (59.4%) is the category that is most performed tooth extraction due to caries. housewife, with a total of 58 patients (35.6%) the highest number of jobs in tooth extraction. Posterior teeth, especially the lower jaw, are the most frequently removed teeth in cases of dental caries, with a total of 91 cases (55.83%).